A double-layer MXene-based aerogel composite phase change film and a preparation method and application thereof
Patent Information
- Application Number
- CN202311758997.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-12-20
AI Technical Summary
然而单独的MXene与氧化石墨烯复合气凝胶在应用于可穿戴设备时无法将转化的热量有效储存起来,仍无法满足于体育训练中热身过渡期保持体温、减少热量散失的实际应用场景和需求
[0032](1)本发明采用真空浸渍法,将相变材料均匀浸渍在MXene基气凝胶薄膜中,并采用冷冻干燥技术建立了双层气凝胶包裹相变材料的结构,其具有良好的光热转化性能和储热性能,同时具备较好的机械性能,可以应用于热身过渡期维持热身效果的可穿戴设备中,以维持体温、减少热量散失。
Smart Images

Figure CN117700828B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aerogel materials technology, and in particular relates to a bilayer MXene-based aerogel composite phase change film, its preparation method and application. Background Technology
[0002] Warm-up exercises, as an important procedure in physical education and training, can effectively improve muscle performance and provide an advantage for subsequent sports activities. However, in physical education and training, college athletes generally face the problem of a warm-up transition period. During this transition period, they may not be able to effectively maintain muscle temperature, leading to a loss of warm-up effects and greatly negating the positive benefits of warm-up.
[0003] Researchers are currently exploring the development of wearable devices to monitor and regulate body temperature in real time to maintain the effectiveness of warm-up exercises, in which photothermal conversion materials play a crucial role. Photothermal conversion is a primitive and direct method of acquiring and utilizing solar energy, in which incident light energy is absorbed by photothermal materials and converted into heat energy for further use.
[0004] MXene is a novel type of two-dimensional transition metal carbide material. Due to its abundant surface chemical groups, excellent electrical activity, high aspect ratio, and strong mechanical properties, it has wide applications in catalysis, supercapacitors, molecular separation, and electromagnetic interference shielding. Furthermore, researchers have discovered that MXene materials also possess unique photothermal conversion properties. CN110090603A discloses an MXene-graphene oxide composite aerogel, its preparation method, and its applications. The composite aerogel prepared through integrated ionic crosslinking exhibits good solar photothermal conversion performance. However, when used alone in wearable devices, the MXene-graphene oxide composite aerogel cannot effectively store the converted heat, failing to meet the practical application scenarios and needs of maintaining body temperature and reducing heat loss during the warm-up transition period in sports training.
[0005] Therefore, there is an urgent need to develop a new type of MXene-based material that combines light conversion capability and energy storage performance, so as to be applied in wearable devices that maintain the warm-up effect during the warm-up transition period. Summary of the Invention
[0006] The purpose of this invention is to provide a bilayer MXene-based aerogel composite phase change film, its preparation method, and its application, so as to meet the usage requirements of wearable devices that maintain the warm-up effect during the warm-up transition period.
[0007] The objective of this invention can be achieved through the following technical solutions:
[0008] A method for preparing a bilayer MXene-based aerogel composite phase change film includes the following steps:
[0009] (1) Preparation of MXene: The MAX phase material was chemically etched to obtain few-layer MXene;
[0010] (2) Preparation of MXene-based aerogel: The MXene, graphene and gel precursor obtained in step (1) are mixed and ultrasonicated and stirred evenly, coated on a polymer base film, and freeze-dried to obtain MXene-based aerogel.
[0011] (3) Preparation of single-layer MXene-based aerogel composite phase change film: The MXene-based aerogel obtained in step (2) is immersed in a phase change material solution under vacuum; the MXene-based aerogel is taken out and dried under vacuum to obtain a single-layer MXene-based aerogel composite phase change film.
[0012] (4) Preparation of bilayer MXene-based aerogel composite phase change film: The surface of the single-layer MXene-based aerogel composite phase change film in step (3) is coated with a mixture of MXene, graphene and gel precursor. After freeze-drying, it is immersed in the phase change material solution again. After taking it out and drying, the bilayer MXene-based aerogel composite phase change film is obtained.
[0013] Further, in step (1), the MAX phase material includes one or more of Ti3AlC2, Ti3SiC2, Ti2AlC or Ti3AlCN, preferably Ti3AlC2.
[0014] Further, in step (2), the mass ratio of MXene, graphene and gel precursor is (0.5-2):1:1, preferably 1:1:1.
[0015] Further, in step (2), the gel precursor includes one or more of bacterial cellulose, chitosan or epoxy resin, preferably bacterial cellulose.
[0016] Furthermore, in step (2), the ultrasound time is 10-30 min, preferably 20 min.
[0017] Furthermore, in step (2), the stirring time is 1-2 hours, preferably 1 hour.
[0018] Further, in step (2), the stirring rate is 200-400 rpm, preferably 300 rpm.
[0019] Furthermore, in step (2), the polymer base membrane is an ultra-high molecular weight PE breathable membrane.
[0020] Furthermore, in step (2), the freeze-drying is carried out under a vacuum of no more than 100 Pa.
[0021] Further, in step (3), the phase transition material includes one or more of PEG-2000 or PEG-4000, preferably PEG-2000.
[0022] Further, in step (3), the specific preparation process of the phase change material solution is as follows: the phase change material is dispersed in water and melted at 80-90℃ until it becomes clear and transparent. The temperature must reach above 80℃ in order for the phase change material to dissolve fully.
[0023] Furthermore, in step (3), the vacuum degree of the impregnation is no greater than 1 Pa.
[0024] Furthermore, in step (3), the impregnation temperature is 80-90°C, preferably 85°C.
[0025] Furthermore, in step (3), the soaking time is 1-3 hours, preferably 2 hours.
[0026] Furthermore, in step (3), the vacuum degree of the drying process is no greater than 1 Pa.
[0027] Furthermore, in step (3), the drying temperature is 80-90℃, preferably 85℃.
[0028] Furthermore, in step (3), the drying time is 3-5 hours, preferably 4 hours.
[0029] The present invention also provides an MXene-based aerogel composite phase change film prepared by the above preparation method.
[0030] This invention also provides an application of a bilayer MXene-based aerogel composite phase change film in the warm-up transition period of sports teaching and training, which is used to maintain muscle temperature and slow down the loss of warm-up effects.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The present invention uses a vacuum impregnation method to uniformly impregnate the phase change material in an MXene-based aerogel film, and uses freeze-drying technology to establish a double-layer aerogel-encapsulated phase change material structure. It has good photothermal conversion performance and heat storage performance, as well as good mechanical properties. It can be applied to wearable devices that maintain the warm-up effect during the warm-up transition period to maintain body temperature and reduce heat loss.
[0033] (2) The MXene-based aerogel of the present invention has a wide range of light absorption wavelengths and an internal photothermal conversion efficiency of nearly 100%. It can absorb and convert clean, renewable solar energy to generate heat energy without the need for additional energy, thus having good photothermal conversion performance. At the same time, by impregnating the phase change material in the porous MXene-based aerogel and establishing a double-layer aerogel structure, the leakage of the phase change material can be effectively reduced.
[0034] (3) The preparation conditions of this invention are mild and the preparation process is easy to implement. It can safely and successfully prepare a double-layer MXene-based aerogel composite phase change film for use in the warm-up transition period of sports teaching and training at room temperature using simple equipment. It has high preparation efficiency and wide applicability. Attached Figure Description
[0035] Figure 1 This is the SEM image of MXene in Example 1.
[0036] Figure 2 This is a schematic diagram of the G-MXene-BC aerogel film in Example 1.
[0037] Figure 3 This is a photograph of the bilayer G-MXene-BC / PEG composite phase change film in Example 1.
[0038] Figure 4 This is a SEM image of the upper surface of the G-MXene-BC aerogel film in Example 1.
[0039] Figure 5 This is an EDS image of the G-MXene-BC aerogel composite phase change film in Example 1.
[0040] Figure 6 The leakage rate curves of the phase change materials in Examples 1-3 and Comparative Example 2 are shown.
[0041] Figure 7 The DSC curves are for the composite phase change films of Examples 1-3 and Comparative Example 2.
[0042] Figure 8 The photothermal conversion and storage curves are for Examples 1-3 and Comparative Examples 1-2.
[0043] Figure 9 The image shows the DSC curve of the 1d-GM-BC / PEG film in Example 1 after undergoing 5 endothermic and exothermic cycles.
[0044] Figure 10 Images showing the mechanical properties of the G-MXene-BC aerogel composite phase change film in Example 1. Detailed Implementation
[0045] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0046] Unless otherwise specified, the reagents, methods, instruments, and equipment used in this invention are conventional in the art. Unless otherwise specified, the reagents and materials used in the following examples are all commercially available and of analytical grade.
[0047] Example 1:
[0048] (1) Preparation of MXene: Weigh 10 mL HCl, 0.8 g LiF and 0.5 g Ti3AlC2 for etching reaction, stir continuously at 35 °C for 24 h, then centrifuge the mixture at 10000 rpm for 12 min, collect the precipitate and sonicate it with deionized water for 30 min, centrifuge the suspension at 3500 rpm for 40 min, and finally dry the collected supernatant in a freeze dryer for 48 h to obtain Ti3C2Tx MXene with few layers.
[0049] (2) Preparation of MXene-based aerogel: 50 mg MXene, 10 mL graphene (5 mg / mL) dispersion, 6.25 g bacterial cellulose solution (0.8 wt%), and 10 mL deionized water were mixed and ultrasonically vibrated (40 kHz) for 20 min, then stirred at 300 rpm for 4 h to obtain a mixture of MXene, graphene, and bacterial cellulose in a mass ratio of 1:1:1. The mixture was then coated onto an ultra-high molecular weight PE breathable membrane (purchased from Dongguan Weiers Technology, VLC502), and the membrane was rapidly solidified in liquid nitrogen before being placed in a freeze dryer for 48 h to obtain MXene-based aerogel (G-MXene-BC aerogel).
[0050] (3) Preparation of monolayer MXene-based aerogel composite phase change film: First, PEG-2000 was dispersed in water and melted at 85°C until clear and transparent. Then, G-MXene-BC aerogel was immersed in the PEG-2000 solution and placed in a vacuum oven at 85°C for 60 min under high vacuum (<1 Pa). The aerogel was then removed and placed on filter paper and dried in a vacuum oven for 4 h, successfully obtaining a monolayer MXene-based aerogel composite phase change film (sG-MXene-BC / PEG).
[0051] (4) Preparation of bilayer MXene-based aerogel composite phase change film: The surface of the single-layer MXene-based aerogel composite phase change film in step (3) is coated with a mixture of MXene, graphene and bacterial cellulose in step (2), freeze-dried and then immersed in PEG-2000 solution again. The operation in step (3) is repeated to finally obtain bilayer MXene-based aerogel composite phase change film (dG-MXene-BC / PEG).
[0052] Example 2:
[0053] (1) Preparation of MXene: Weigh 10 mL HCl, 0.8 g LiF and 0.5 g Ti3AlC2 for etching reaction, stir continuously at 35 °C for 24 h, then centrifuge the mixture at 10000 rpm for 12 min, collect the precipitate and sonicate it with deionized water for 30 min, centrifuge the suspension at 3500 rpm for 40 min, and finally dry the collected supernatant in a freeze dryer for 48 h to obtain Ti3C2Tx MXene with few layers.
[0054] (2) Preparation of MXene-based aerogel: 25 mg MXene, 10 mL graphene (5 mg / mL) dispersion, 6.25 g bacterial cellulose solution (0.8 wt%), and 10 mL deionized water were mixed and ultrasonically vibrated (40 kHz) for 20 min, and then stirred at 300 rpm for 4 h to obtain a mixture of MXene, graphene, and bacterial cellulose in a mass ratio of 1:1:1. The mixture was then coated onto an ultra-high molecular weight PE breathable membrane (purchased from Dongguan Weiers Technology, VLC502), and the membrane was rapidly solidified in liquid nitrogen and then placed in a freeze dryer for 48 h to obtain MXene-based aerogel (G-MXene-BC aerogel).
[0055] (3) Preparation of monolayer MXene-based aerogel composite phase change film: First, PEG-2000 was dispersed in water and melted at 85°C until clear and transparent. Then, G-MXene-BC aerogel was immersed in the PEG-2000 solution and placed in a vacuum oven at 85°C for 60 min under high vacuum (<1 Pa). The aerogel was then removed and placed on filter paper and dried in a vacuum oven for 4 h, successfully obtaining a monolayer MXene-based aerogel composite phase change film (sG-MXene-BC / PEG).
[0056] (4) Preparation of bilayer MXene-based aerogel composite phase change film: The surface of the single-layer MXene-based aerogel composite phase change film in step (3) is coated with a mixture of MXene, graphene and bacterial cellulose in step (2), freeze-dried and then immersed in PEG-2000 solution again. The operation in step (3) is repeated to finally obtain bilayer MXene-based aerogel composite phase change film (dG-MXene-BC / PEG).
[0057] Example 3:
[0058] (1) Preparation of MXene: Weigh 10 mL HCl, 0.8 g LiF and 0.5 g Ti3AlC2 for etching reaction, stir continuously at 35 °C for 24 h, then centrifuge the mixture at 10000 rpm for 12 min, collect the precipitate and sonicate it with deionized water for 30 min, centrifuge the suspension at 3500 rpm for 40 min, and finally dry the collected supernatant in a freeze dryer for 48 h to obtain Ti3C2Tx MXene with few layers.
[0059] (2) Preparation of MXene-based aerogel: 100 mg MXene, 10 mL graphene (5 mg / mL) dispersion, 6.25 g bacterial cellulose solution (0.8 wt%), and 10 mL deionized water were mixed and ultrasonically vibrated (40 kHz) for 20 min, and then stirred at 300 rpm for 4 h to obtain a mixture of MXene, graphene, and bacterial cellulose in a mass ratio of 1:1:1. The mixture was then coated onto an ultra-high molecular weight PE breathable membrane (purchased from Dongguan Weiers Technology, VLC502), and the membrane was rapidly solidified in liquid nitrogen and then placed in a freeze dryer for 48 h to obtain MXene-based aerogel (G-MXene-BC aerogel).
[0060] (3) Preparation of monolayer MXene-based aerogel composite phase change film: First, PEG-2000 was dispersed in water and melted at 85°C until clear and transparent. Then, G-MXene-BC aerogel was immersed in the PEG-2000 solution and placed in a vacuum oven at 85°C for 60 min under high vacuum (<1 Pa). The aerogel was then removed and placed on filter paper and dried in a vacuum oven for 4 h, successfully obtaining a monolayer MXene-based aerogel composite phase change film (sG-MXene-BC / PEG).
[0061] (4) Preparation of bilayer MXene-based aerogel composite phase change film: The surface of the single-layer MXene-based aerogel composite phase change film in step (3) is coated with a mixture of MXene, graphene and bacterial cellulose in step (2), freeze-dried and then immersed in PEG-2000 solution again. The operation in step (3) is repeated to finally obtain bilayer MXene-based aerogel composite phase change film (dG-MXene-BC / PEG).
[0062] Comparative Example 1:
[0063] This comparative example provides a G-MXene-BC aerogel without the addition of a phase transition material.
[0064] (1) Preparation of MXene: Weigh 10 mL HCl, 0.8 g LiF and 0.5 g Ti3AlC2 for etching reaction, stir continuously at 35 °C for 24 h, then centrifuge the mixture at 10000 rpm for 12 min, collect the precipitate and sonicate it with deionized water for 30 min, centrifuge the suspension at 3500 rpm for 40 min, and finally dry the collected supernatant in a freeze dryer for 48 h to obtain Ti3C2Tx MXene with few layers.
[0065] (2) Preparation of MXene-based aerogel: 50 mg MXene, 10 mL graphene (5 mg / mL) dispersion, 6.25 g bacterial cellulose solution (0.8 wt%), and 10 mL deionized water were mixed and ultrasonically vibrated (40 kHz) for 20 min, then stirred at 300 rpm for 4 h to obtain a mixture of MXene, graphene, and bacterial cellulose in a mass ratio of 1:1:1. The mixture was then coated onto an ultra-high molecular weight PE breathable membrane (purchased from Dongguan Weiers Technology, VLC502), and the membrane was rapidly solidified in liquid nitrogen before being placed in a freeze dryer for 48 h to obtain MXene-based aerogel (G-MXene-BC aerogel).
[0066] Comparative Example 2:
[0067] This comparative example provides a single-layer MXene-based aerogel composite phase change film.
[0068] (1) Preparation of MXene: Weigh 10 mL HCl, 0.8 g LiF and 0.5 g Ti3AlC2 for etching reaction, stir continuously at 35 °C for 24 h, then centrifuge the mixture at 10000 rpm for 12 min, collect the precipitate and sonicate it with deionized water for 30 min, centrifuge the suspension at 3500 rpm for 40 min, and finally dry the collected supernatant in a freeze dryer for 48 h to obtain Ti3C2Tx MXene with few layers.
[0069] (2) Preparation of MXene-based aerogel: 50 mg MXene, 10 mL graphene (5 mg / mL) dispersion, 6.25 g bacterial cellulose solution (0.8 wt%), and 10 mL deionized water were mixed and ultrasonically vibrated (40 kHz) for 20 min, then stirred at 300 rpm for 4 h to obtain a mixture of MXene, graphene, and bacterial cellulose in a mass ratio of 1:1:1. The mixture was then coated onto an ultra-high molecular weight PE breathable membrane (purchased from Dongguan Weiers Technology, VLC502), and the membrane was rapidly solidified in liquid nitrogen before being placed in a freeze dryer for 48 h to obtain MXene-based aerogel (G-MXene-BC aerogel).
[0070] (3) Preparation of monolayer MXene-based aerogel composite phase change film: First, PEG-2000 was dispersed in water and melted at 85°C until clear and transparent. Then, G-MXene-BC aerogel was immersed in the PEG-2000 solution and placed in a vacuum oven at 85°C for 60 min under high vacuum (<1 Pa). The aerogel was then removed and placed on filter paper and dried in a vacuum oven for 4 h, successfully obtaining a monolayer MXene-based aerogel composite phase change film (sG-MXene-BC / PEG).
[0071] The present invention conducted the following tests on Examples 1-3 and Comparative Examples 1-2:
[0072] (1) Surface morphology characterization: The surface morphology of the upper surface of the few-layer Ti3C2Tx MXene and G-MXene-BC aerogels was characterized by scanning electron microscopy (SEM).
[0073] (2) Elemental analysis: The elemental analysis of the bilayer MXene-based aerogel composite phase change film of Example 1 was performed using an X-ray energy dispersive spectrometer.
[0074] (3) Leakage rate test: Under a xenon lamp simulating a sunlight intensity source, the leakage rate of the phase change material was detected by using filter paper to absorb the leaked material in Example 1.
[0075] (4) Thermal performance testing: Differential scanning calorimetry (DSC) was used to test the thermal performance of Examples 1-3 and Comparative Example 2.
[0076] (5) Photothermal conversion test: Under a xenon lamp simulating a sunlight intensity source, the photothermal conversion capability of Example 1 was recorded by an infrared camera under a light cycle.
[0077] (6) Mechanical performance test: The three-point bending performance of Example 1 was tested by using an electronic universal testing machine.
[0078] Figure 1 The SEM images of MXene show that the present invention successfully etched MAX material and obtained few-layer MXene material. Figure 2 The thin film images show that the MXene-based aerogel has initially acquired a stable morphology and a certain degree of flexibility. Figure 3 As can be seen from the actual thin film image, the bilayer MXene-based aerogel composite phase change film prepared in Example 1 has a size of approximately 5×5cm and also exhibits stable morphology and flexibility. Figure 4 The SEM images show that the MXene-based aerogel film has a large pore size and a good spatial structure, which is beneficial for the impregnation of phase change materials.
[0079] Figure 5 The EDS images show that the main components of the film are Ti, C, O and F, indicating the successful preparation of the MXene-based aerogel composite phase change film. All the elements have no effect on the human body and have good biosafety. Figure 6 The leakage rate curves show that the single-layer MXene-based aerogel composite phase change film of Comparative Example 2 exhibits a higher PEG leakage rate, while the double-layer MXene-based aerogel composite phase change films of Examples 1-3 have lower leakage rates. Furthermore, the double-layer MXene-based aerogel composite phase change film of Example 1 shows the best impregnation and encapsulation effect on PEG.
[0080] Figure 7 The DSC curves show that the melting temperature of the GM-BC / PEG film fluctuates between 52-56℃, with little change compared to pure PEG2000. It is also evident that with increasing MXene mass fraction, the melting enthalpy and crystallization enthalpy of the composite phase change film exhibit a regular upward trend, displaying a higher peak phase change temperature and a more concentrated phase change temperature range. Since PEG plays a major role in heat storage in the composite material, the aerogel structure of the MXene-based aerogel composite phase change film with a larger mass fraction provides excellent spatial structural conditions for the impregnation of phase change materials, allowing PEG to better perform its heat storage function.
[0081] Figure 8 The photothermal conversion and storage curves show that the introduction of phase change materials into the MXene-based aerogel film can effectively slow down the heat loss after the loss of light conditions, and the temperature rise curve of Example 1 shows that it can reach the conditions for PEG to exert its endothermic melting effect more quickly and maintain the temperature at around 50°C, which meets the personal thermal management function required by smart temperature-controlled wearable devices.
[0082] Figure 9The DSC curves of the film in Example 1 after five endothermic and exothermic cycles showed no significant difference before and after multiple cycles, and the curves of the five cycles highly overlapped. This indicates that the MXene-based aerogel composite phase change film of Example 1 has good cycling stability and maintains stable chemical properties even under continuous and frequent endothermic and exothermic cycles in the experimental environment.
[0083] Figure 10 The mechanical test images show that the MXene-based aerogel composite phase change film of Example 1 has good flexibility properties and can be bent without breaking under common external forces. This provides a good mechanical basis for its application as a smart wearable device in sports teaching and training.
[0084] In summary, the bilayer MXene-based aerogel composite phase change film of this invention exhibits excellent photothermal conversion and heat storage properties, while also possessing good mechanical properties. This meets the requirements of smart wearable devices for conforming to human muscles, maintaining body temperature, and reducing heat loss, and provides more specific practical strategies for the application of smart wearable devices in sports teaching and training.
[0085] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a bilayer MXene-based aerogel composite phase change film, characterized in that, Includes the following steps: (1) Preparation of MXene: The MAX phase material was chemically etched to obtain few-layer MXene; (2) Preparation of MXene-based aerogel: The MXene, graphene and gel precursor obtained in step (1) are mixed and ultrasonicated and stirred evenly, coated on a polymer base film, and freeze-dried to obtain MXene-based aerogel. (3) Preparation of single-layer MXene-based aerogel composite phase change film: The MXene-based aerogel obtained in step (2) is immersed in a phase change material solution under vacuum; the MXene-based aerogel is taken out and dried under vacuum to obtain a single-layer MXene-based aerogel composite phase change film. (4) Preparation of bilayer MXene-based aerogel composite phase change film: The surface of the single-layer MXene-based aerogel composite phase change film in step (3) is coated with a mixture of MXene, graphene and gel precursor. After freeze-drying, it is immersed in the phase change material solution again. After taking it out and drying, the bilayer MXene-based aerogel composite phase change film is obtained.
2. The method for preparing a bilayer MXene-based aerogel composite phase change film according to claim 1, characterized in that, In step (1), the MAX phase material includes one or more of Ti3AlC2, Ti3SiC2, Ti2AlC or Ti3AlCN.
3. The method for preparing a bilayer MXene-based aerogel composite phase change film according to claim 1, characterized in that, In step (2), the mass ratio of MXene, graphene and gel precursor is (0.5-2):1:
1.
4. The method for preparing a bilayer MXene-based aerogel composite phase change film according to claim 1, characterized in that, In step (2), the gel precursor includes one or more of bacterial cellulose, chitosan or epoxy resin.
5. The method for preparing a bilayer MXene-based aerogel composite phase change film according to claim 1, characterized in that, In step (2), the ultrasound duration is 10-30 minutes; The stirring time is 1-2 hours, and the stirring speed is 200-400 rpm; The freeze-drying is carried out under a vacuum of no more than 100 Pa.
6. The method for preparing a bilayer MXene-based aerogel composite phase change film according to claim 1, characterized in that, In step (3), the phase transition material includes one or more of PEG-2000 or PEG-4000.
7. The method for preparing a bilayer MXene-based aerogel composite phase change film according to claim 1, characterized in that, In step (3), the specific preparation process of the phase change material solution is as follows: disperse the phase change material in water and melt it at 80-90℃ until it becomes clear and transparent.
8. The method for preparing a bilayer MXene-based aerogel composite phase change film according to claim 1, characterized in that, In step (3), the vacuum degree of the impregnation is no greater than 1 Pa, the impregnation temperature is 80-90℃, and the impregnation time is 1-3 h; The drying process involves a vacuum degree of no more than 1 Pa, a drying temperature of 80-90℃, and a drying time of 3-5 hours.
9. A bilayer MXene-based aerogel composite phase change film prepared by the preparation method according to any one of claims 1-8.
10. The application of the bilayer MXene-based aerogel composite phase change film as described in claim 9 in the warm-up transition period of physical education teaching and training.
Citation Information
Patent Citations
Improved graphene aerogel and polyethylene glycol composite phase change material and preparation method thereof
CN114525112A
Graphene-bacterial cellulose-MXene hybrid aerogel and preparation thereof, and epoxy resin-based composite material and preparation thereof
CN116144077A